2012
DOI: 10.1016/j.ydbio.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 mediates store-operated Ca2+ entry during fertilization in mammalian oocytes

Abstract: The presence of the store-operated Ca(2+) entry channel Orai1 and its function in signal transduction during fertilization have been investigated in mammalian oocytes using the pig as a model. RT-PCR cloning and sequence analysis revealed that Orai1 is expressed in the oocytes with a coding sequence of 921bp. After indirect immunocytochemistry or the overexpression of EGFP-tagged Orai1, the fluorescent signal was present primarily in the cell cortex consistent with plasma membrane localization of the protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 46 publications
2
23
1
Order By: Relevance
“…Sperm-derived PLCz cleaves PIP 2 and generates InsP 3 that triggers Ca 2C release from the endoplasmic reticulum. Results in pig oocytes seem to indicate that STIM1 senses store depletion and transmits the empty signal to the plasma membrane where it opens ORAI1 channels and induces storeoperated Ca 2C entry (Lee et al 2012, Wang et al 2012. Recent data from mouse oocytes did not support the involvement of a store-operated entry mechanism (Miao et al 2012, Takahashi et al 2013.…”
Section: C Influx During Fertilizationmentioning
confidence: 98%
See 1 more Smart Citation
“…Sperm-derived PLCz cleaves PIP 2 and generates InsP 3 that triggers Ca 2C release from the endoplasmic reticulum. Results in pig oocytes seem to indicate that STIM1 senses store depletion and transmits the empty signal to the plasma membrane where it opens ORAI1 channels and induces storeoperated Ca 2C entry (Lee et al 2012, Wang et al 2012. Recent data from mouse oocytes did not support the involvement of a store-operated entry mechanism (Miao et al 2012, Takahashi et al 2013.…”
Section: C Influx During Fertilizationmentioning
confidence: 98%
“…Both indirect immunocytochemistry and overexpression of fluorescently tagged ORAI1 revealed that ORAI1 was present mostly in the cell cortex consistent with plasma membrane localization. Expression of ORAI1 decreased in pig eggs during maturation with STIM1 levels remaining fairly constant (Wang et al 2012); this was different in mouse eggs where ORAI1 expression levels were unaltered during maturation while STIM1 was expressed only at very low levels in the GV-stage oocyte (Gó mez-Fernández et al 2012). Despite these species-specific differences in the expression levels of these signaling proteins, the effect of the changes seems to be the same in both species: to enhance the small store-operated Ca 2C influx measured in GV-stage oocytes to a much higher level by the time the oocytes complete maturation and are ready for fertilization.…”
Section: C Influx During Fertilizationmentioning
confidence: 99%
“…Recently, they have been identified in pig and mouse oocytes and their involvement in store-operated calcium entry has also been demonstrated [GomezFernandez et al 2009;Koh et al 2009;Yu et al 2009]. In porcine, Orai1 expression decreased during oocyte maturation along with the increasing ability to generate a large calcium influx after store depletion [Wang et al 2012]. In addition, down-regulation of Orai1 expression by siRNA microinjection blocked calcium influx after store depletion and subsequent calcium add-back.…”
Section: Mammalsmentioning
confidence: 99%
“…Over-expression of Orai1 in the oocytes modified store-operated calcium entry and had an inhibitory effect on the calcium fertilization signal. Co-over-expression of Orai1 and STIM1 led to a dramatic increase in calcium entry after store depletion [Wang et al 2012].…”
Section: Mammalsmentioning
confidence: 99%
“…Their up regulation has been shown to induce a dramatic increase in Ca 2+ entry after intracellular store depletion. Interestingly, in pig Orai1 expression decreases during oocyte maturation (Wang et al, 2012) whereas its down regulation inhibit Ca 2+ influx after store depletion and the Ca 2+ oscillations induced by the fertilizing sperm. On the other hand up regulation of Orai1 in the oocytes also modifies store-operated Ca 2+ entry and plays an inhibitory effect on the fertilization Ca 2+ signal, that results moreover in a long term negative effect on following embryo development.…”
Section: The Oocytementioning
confidence: 98%